Design and Implementation of Synthesizable 32-bit Four Stage Pipelined RISC Processor in FPGA Using Verilog/VHDL - Poduel, Bikash; Kansakar, Prasanna; Chhetri, Sujit R.; Joshi, Shashidhar Ram (Nepal Journal of Science and Technology, 2015)
This paper is delineating the design and implementation of high performance, synthesizable 32-bit pipelined Reduced Instruction Set Computer (RISC) Core. The design of the Harvard Architecture based 32-bit RISC Core involves design of 32-bit Data-path Unit, Control Unit, 32-bit Instruction Memory, 32-bit Data Memory, Register file with each register of size 32 bit. The processor is divided into Fetch, Decode, Execute and Write Back block in order to implement a four-stage pipeline. A 2*16 LCD is connected to the processor IO block to show the instruction execution sequence for demonstration in FPGA. The RISC Core is designed using Verilog HDL and VHDL and is tested in ISIM Simulator. The implementation of the processor is done in a Spartan 3E Starter Board using Xilinx ISE 14.7. All of the instructions incorporated with the processor have been tested successfully both in simulation and hardware implementation in FPGA. DOI: http://dx.doi.org/10.3126/njst.v15i1.12021 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 81-88